Analisis Integrasi Big Data dan IoT untuk Meningkatkan Kualitas Layanan Kesehatan Berbasis Teknologi - Eimanisura Sinaga; Rindu Basnella; Rehuelli Madiya; Veronica Rompas (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The development of information technology has had a significant impact on the healthcare sector, particularly in improving the efficiency and quality of services. Technologies such as Big Data and the Internet of Things (IoT) enable the collection and analysis of large volumes of medical data as well as real-time patient monitoring. This study aims to analyze how the integration of Big Data and IoT can enhance the quality of healthcare services, with a focus on their impact on patient care and hospital operational efficiency. The research method used is a literature review, involving the collection and analysis of data from various sources such as scientific journals, articles, and related research reports. The results indicate that hospitals that have implemented these technologies have experienced significant improvements in several aspects, including increased diagnostic accuracy, reduced service delays, and more efficient resource management. Real-time patient monitoring through IoT devices enables faster medical decision-making, while Big Data analytics helps predict disease patterns and medical needs. However, the challenges faced include data security issues, infrastructure limitations, and shifts in healthcare practice paradigms. In conclusion, the integration of Big Data and IoT can improve the quality of healthcare services, but addressing the existing challenges is essential to optimize its implementation in the healthcare sector.